Pengaruh Pencapaian Biologi dan Kimia Peringkat SPM dalam Meramal Pencapaian Pelajar bagi Subjek Biologi Manusia (Sains Humanika, 2017)
The purpose of this study is to identify differences in the results of the semester examinations for the Human Biology subject of the Diploma in Medical Laboratory Technology (DMLT) program for science and non-science stream students at the Sijil Pelajaran Malaysia (SPM) level as well as the achievement of male and female students. Furthermore, this study is also intended to predict the results of the Human Biology subject based on the SPM subjects of Biology and Chemistry. This study is a quantitative study involving the analysis of students' Human Biology subjects for the July-December 2012 session using multiple regression analysis with SPM results as independent variables. The sample used was 40 students who were randomly selected from the College of Medical Laboratory Technology, Kuala Lumpur, and the Allied Health Science College, Kuching, Sarawak. The results of the data analysis showed that the achievement of students from the science stream in the Human Biology subject was better (p
Keywords: Students' achievement predictor; human biology; biology; chemistry